2016
DOI: 10.3109/08958378.2015.1123331
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Asian dust on asthma by socioeconomic status using national health insurance claims data in Korea

Abstract: Our study confirms that Asian dust events result in an increased number of asthma-related visits to medical institutions. This effect differed by socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Genes showing differential expression included those involved in the cell cycle, cholesterol biosynthesis, and platelet activation. A more recent study partially confirmed these results [ 114 ]. In fact, analysis of the liver proteome and transcriptome showed upregulation of several enzymes involved in fatty acid and cholesterol metabolism upon CS inhalation.…”
Section: Apoe −/− Mouse Model To Investigate Toxicsupporting
confidence: 63%
See 2 more Smart Citations
“…Genes showing differential expression included those involved in the cell cycle, cholesterol biosynthesis, and platelet activation. A more recent study partially confirmed these results [ 114 ]. In fact, analysis of the liver proteome and transcriptome showed upregulation of several enzymes involved in fatty acid and cholesterol metabolism upon CS inhalation.…”
Section: Apoe −/− Mouse Model To Investigate Toxicsupporting
confidence: 63%
“…The effects of CS exposure and smoking cessation were also determined on hepatic lipid, transcriptomic, and proteomic profiles in Apoe −/− mice [ 114 , 116 , 118 ]. De Leon and colleagues [ 118 ] showed that the concentrations of many lipids, including free cholesterol, ceramides, and sphingomyelin, decreased in the liver of Apoe −/− mice following smoking cessation, although the triacylglycerol concentration increased.…”
Section: Apoe −/− Mouse Model To Investigate Toxicmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Due to increase in incidence and prevalence of asthma, direct and indirect costs of this disease are amplifying. 4,5 Present study, was conducted with the aim of calculating the direct costs of pediatric asthma in Tehran-Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Asian sand dust (ASD) (known as Kosa aerosol) originating from the arid deserts of Mongolia and China, causes severe air pollution annually in the Asia-Pacific area, including China, Korea, and Japan [ 1 , 2 ]. Epidemiological studies of ASD show that human exposure to ambient ASD particles is associated with an increase in pulmonary and cardiovascular problems and an increase in daily mortality in Korea [ 3 , 4 ], Taiwan [ 5 ], and Japan [ 6 , 7 ]. The frequency and scale of dust events giving rise to ASD aerosols have increased rapidly in the east Asian region since 2000 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%